1983
DOI: 10.1530/jrf.0.0670173
|View full text |Cite
|
Sign up to set email alerts
|

Response of sows to oestradiol benzoate treatment after weaning at two stages of lactation

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Finally, in lactating sows, the hormones and neurotransmitters associated with suckling could block the discharge of GnRH and that of LH in response to high levels of oestrogens. In weaned sows, the duration of lactation influences the responsiveness to OB; the amplitude of the oestrogen-induced LH surge is higher after 35 than after 21 or 10 d of lactation (Edwards and Foxcroft, 1983b;Kirkwood et al, 1984b).…”
Section: Ovarian Activitymentioning
confidence: 99%
“…Finally, in lactating sows, the hormones and neurotransmitters associated with suckling could block the discharge of GnRH and that of LH in response to high levels of oestrogens. In weaned sows, the duration of lactation influences the responsiveness to OB; the amplitude of the oestrogen-induced LH surge is higher after 35 than after 21 or 10 d of lactation (Edwards and Foxcroft, 1983b;Kirkwood et al, 1984b).…”
Section: Ovarian Activitymentioning
confidence: 99%
“…Concentrations of LH are maximally suppressed by nursing of piglets and increase following weaning, but not after ovariectomy during lactation (6,10,11,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…While consideration of the LH response data indicated that higher oestradiol benzoate doses may be required, particularly after short lactations, Hausler et al (1980) concluded that low pregnancy rates after treatment with PMSG-hCG at 5 or 10 days post partum were due to decreased ovarian responsiveness and/or an unfavourable uterine environment. Also, prolonged high plasma levels of oestrogen have been shown to prevent the periovulatory rise in plasma FSH concentrations (Edwards & Foxcroft, 1983) and high post-mating oestrogen concentrations may adversely affect tubai egg transport, with consequently increased embryo mortality (Varley, Atkinson & Ross, 1981). Such factors may have contributed to the reduction in pregnancy rates of sows in Group S-E2 compared with that of sows in Group S-C in Exp.…”
Section: Discussionmentioning
confidence: 99%
“…Further, short lactations have been shown to be associated with reduced gonadotrophin secretion at the first post-weaning oestrus (Edwards & Foxcroft, 1983 ;Kirkwood et al, 1984). The reasons for this reduction of gonadotrophin secretion and its physiological consequences are not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation